Y M. Yeung y David K. Y. Chu (comps.). Guangdong. A Survey of a Province Undergoing Rapid Change. Hong Kong: The Chinese University Press, 1998. 2a ed. (1a ed., 1994). - Rodríguez y Rodríguez, María Teresa; Yeung, Yue-man; Chu, David K. Y. (Estudios de Asia y África, 1999)
-